Operative and Midterm Outcomes of the Fenestrated Anaconda Stent-Graft in the Endovascular Treatment of Juxtarenal, Suprarenal, and Type IV Thoracoabdominal Aortic Aneurysms. (December 2016) - Kotelis, Drosos; Schleimer, Karina; Foldenauer, Christina; Jalaie, Houman; Grommes, Jochen; Jacobs, Michael J.; Kalder, Johannes
Purpose: To report operative and midterm outcomes of fenestrated endovascular aneurysm repair (FEVAR) with the Anaconda device.Methods: A retrospective analysis was conducted of 39 consecutive patients (median age 74 years; 36 men) treated with the fenestrated Anaconda stent-graft between July 2011 and December 2015 at a single center. Indications for FEVAR were abdominal aortic aneurysms (AAAs) with neck anatomy unsuitable for a standard stent-graft. Median infrarenal neck length was 4 mm (range 0–9). Four (10%) patients presented with type IV thoracoabdominal aortic aneurysm (TAAA), 12 (31%) with suprarenal aneurysms, and 23 (59%) with juxtarenal aneurysms. Four (10%) patients had previous infrarenal aortic repair. Five (13%) patients had an infrarenal neck angulation >60°. A total of 106 fenestrations were incorporated into the stent-grafts (73 renal arteries, 25 superior mesenteric arteries, and 8 celiac trunks). Technical success, perioperative and midterm mortality and morbidity, target vessel patency, endoleaks, and reinterventions were documented.Results: Technical success was 95% (37/39). Three (8%) patients died in-hospital from mesenteric embolism in 2 and renal artery rupture with consequent multiorgan failure in 1. Two (5%) patients suffered an intraoperative embolic stroke. During a median follow-up of 33 months (range 4–55), adjunctive maneuvers were performed in 9 (23%) patients, including reintervention for type II endoleak with enlarged aneurysm sac in 2 (5%). Four additional patients died of causes unrelated to the aortic pathology (overall mortality 18%). In 34 (94%) of the 36 patients seen in follow-up, aneurysm sac size was stable or decreased. Target vessel stent patency was 99% (95/96).Conclusion: FEVAR with the Anaconda device delivers satisfactory short-term technical and clinical success rates in patients with juxtarenal, suprarenal, and type IV TAAA. Midterm efficacy and durability with respect to aneurysm sac regression and target vessel patency appear very good. Overall mortality and the need for reintervention were significant in this patient cohort.